2018
DOI: 10.3389/fmicb.2018.00294
|View full text |Cite
|
Sign up to set email alerts
|

Drought Legacy Effects on the Composition of Soil Fungal and Prokaryote Communities

Abstract: It is increasingly acknowledged that climate change is influencing terrestrial ecosystems by increased drought and rainfall intensities. Soil microbes are key drivers of many processes in terrestrial systems and rely on water in soil pores to fulfill their life cycles and functions. However, little is known on how drought and rainfall fluctuations, which affect the composition and structure of microbial communities, persist once original moisture conditions have been restored. Here, we study how simulated shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 92 publications
9
117
0
Order By: Relevance
“…Alternatively, the vegetation leaves have also been suggested as sources of atmospheric SCs (Bozzetti et al, 2016;Golly et al, 2018;Jia et al, 2010;Myriokefalitakis et al, 2017;Pashynska et al, 2002;Sullivan et al, 2011;Verma et al, 2018;Wan et al, 2019). In fact, vascular plant leaf surfaces is an important habitat for endophytic and epiphytic microbial communities (Kembel and Mueller, 2014;Lindow and Brandl, 2003;Lymperopoulou et al, 2016;Mhuireach et al, 2016;Whipps et al, 2008). Our results are more in agreement with a dominant atmosphere entrance process closely linked to vegetation, which is more homogeneous than topsoil at the climatic regional scale.…”
Section: Data Analysessupporting
confidence: 84%
See 2 more Smart Citations
“…Alternatively, the vegetation leaves have also been suggested as sources of atmospheric SCs (Bozzetti et al, 2016;Golly et al, 2018;Jia et al, 2010;Myriokefalitakis et al, 2017;Pashynska et al, 2002;Sullivan et al, 2011;Verma et al, 2018;Wan et al, 2019). In fact, vascular plant leaf surfaces is an important habitat for endophytic and epiphytic microbial communities (Kembel and Mueller, 2014;Lindow and Brandl, 2003;Lymperopoulou et al, 2016;Mhuireach et al, 2016;Whipps et al, 2008). Our results are more in agreement with a dominant atmosphere entrance process closely linked to vegetation, which is more homogeneous than topsoil at the climatic regional scale.…”
Section: Data Analysessupporting
confidence: 84%
“…These results highlight that ambient air temperature and humidity are key meteorological drivers of the annual variation cycles of polyol and glucose concentrations. Hot and dry ambient air conditions may decrease the metabolic activity of the microorganisms (e.g., microbial growth and sporulation) (Fang et al, 2018;Liang et al, 2013;Meisner et al, 2018). Finally, maximum ambient concentration levels for both SC and cellulose are observed in excellent temporal agreement with the harvest periods (late summer) at the OPE-ANDRA site (Fig.…”
Section: Specific Case Of a Highly Impacted Agricultural Areamentioning
confidence: 64%
See 1 more Smart Citation
“…Previous studies in unburned soils also found legacy effects of short‐ or long‐lasting drought on microbial biomass, activity, and community structure (Evans & Wallenstein, : De Vries, Liiri, Bjørnlund, Bowker et al, ; De Vries, Liiri, Bjørnlund, Setälä et al, ; Martiny et al, ; Meisner, Jacquiod, Snoek, Hooven, & Putten, ; Legay et al, ). On the other hand, Rousk et al () reported no legacy effects of long‐term experimental summer drought on microbial community size, composition, growth rates, or respiration rates.…”
Section: Discussionmentioning
confidence: 87%
“…The relative abundance of these bacterial communities was still lower compared to during the wet phases of environmental watering ( Table 2). Re-wetting has been known to quickly alter microbial abundance in wetland soils (Meisner et al, 2018). However, environmental watering may have permanently altered the microbial community and carbon cycling within this ecosystem, as some community differences were still seen after 1 Month of watering.…”
Section: One Month After Environmental Wateringmentioning
confidence: 99%